Innovation of Non-Learning Activities in Fostering Student Discipline and Participation during Ramadan - Marini Magdalena; Andriansyah Andriansyah; Sri Ismawati; Berlian Sheila Kusuma; Nurdiansyah Nurdiansyah; Defi Maulida; Ifdah Ifdah; Ruaida Ruaida; Muhammad Sheva Sobriaz Azhari (CV. Rayyan Dwi Bharata, 2025)
This study examines the implementation of structured non-teaching activities during the Ramadan period to enhance students’ discipline, participation, and social engagement in a primary school context. The research addresses the limited attention given to short-term, intensive extracurricular programs conducted within teaching practice settings. A qualitative case study design was employed, with data collected through observations, semi-structured interviews, and field documentation involving 54 students from grades 1 to 6 at SDN Beberan 2. The program consisted of a series of competitions, including Sambung Ayat, Adzan, Kaligrafi, and Fashion Show, conducted over three consecutive days. The findings indicate that these activities contributed positively to students’ active participation, confidence, and behavioral discipline. Performance data showed consistent achievement across activities, supported by structured assessment instruments that enabled objective evaluation of students’ competencies. Qualitative analysis further revealed that students perceived the activities as engaging and meaningful, providing opportunities for self-expression, collaboration, and experiential learning. The activities also fostered social interaction and reduced anxiety in participating in public performances. However, challenges such as differences in student readiness, time limitations, and varying skill levels were identified, highlighting the need for guided facilitation and adaptive instructional support. This study concludes that structured non-teaching activities conducted in a short-term program can serve as an effective complementary approach to formal learning by promoting students’ discipline, participation, and social development when supported by appropriate planning and assessment strategies.